Rancang Bangun Turbin Angin Aksis Vertikal Sebagai Alternatif Catu Daya Pada Perlintasan Sebidang Perkeretaapian - Darmawan, Arief; Winjaya, Fathurrozi (Politeknik Perkeretaapian Indonesia Madiun, 2019)
Level crossing security gate equipment is a railroad operating facility that requires an electrical energy source. The use of fossil fuels as fuel for power plants is running low, according to estimates the amount of fossil fuel reserves will be exhausted in about 83 years. To save fossil fuel reserves, we need a backup energy source from renewable energy sources such as wind energy. Wind energy around the railroad track has enormous potential to be used as electrical energy. Micro wind electricity builders in this study use wind turbines with vertical blades and wind directors in the form of fins. Based on the results of research and testing it can be concluded that the vertical wind turbine that is implemented to supply crossing door safety equipment can charge batteries with an average charging current of 3.28 A at an average wind speed of 3.90 m / s and rotation of 278 rpm and produces 39.45 watts of power and 394.5 watts of total energy so that it can charge a 75Ah / 12 volt battery for 22 hours